A sectoral model extension to STREAM - Noel Rapa (Central Bank of Malta, 2020)
This paper proposes a sectoral extension to STREAM, the Bank's main macroeconometric model. The extension documented in this paper borrows heavily from linking integration strategies prevalent in literature. The approach utilised here however, differs in two main ways when compared to existing integrated models. Unlike other integrated models the model proposed in this paper makes use of three modules and two different integration strategies, making it extremely flexible and able to answer a range of policy oriented questions. Secondly, this model utilises a fully-fledged macroeconometric model in its EC module, allowing for more realistic dynamics when compared to the single equation EC models used in literature.
Keywords: C51; C67; R15; 330; Econometrics; Input-Output model; Integrated models; Malta